Study the Effect of Ultraviolet (UV) on Mutagenicity of Pseudomonas Aeruginosa Isolated from Burn Wound Infections - Bushra hindi Saleh; Reem Neam Ibrahim; Hasan A. Aal Owaif (Indian Journal of Forensic Medicine & Toxicology, 2021)
Burn wound infections are regarded as one of the serious complications occurs in the acute period afterinjury and leads to high morbidity and mortality. Pseudomonas aeruginosa plays a prominent role as anetiological agent involved in serious infections of burn and wounds.During this study, a total of (52) samples were taken from patients suffering from burn wound infectionsin (2) hospital in Baghdad from 1/9/2019 to 1/12/2019 for isolation of pseudomonas aeruginosa. Resultsreveals that (31) isolate (59.6%) were gave typical morphological characteristics and biochemical test thatrelated to Pseudomonas aeruginosa. Five Pseudomonas aeruginosa isolates were subject to antimicrobialsusceptibility test that was done according to NCCLS. Results of Antibiotic susceptibility test for pseudomonasaeruginosa isolates reveals that 100% of them were sensitive to ciprofloxacin and Norfloxacin while 100%of the isolates were resistant to ampicillin ,cefixime ,Erythromycin, Naldixic acid , chloramphenicol andbacitracin.Mutagenesis of Pseudomonas aeruginosa PS1 isolate by UV irradiation was done for (60,120,240,300 ) Sec.Results of mutation to ( PS1) isolate revealed that exposure to UV irradiation from (60-300) Sec leads to decreasein the viability of bacterial cells but increase in the sensitivity of PS1 isolate to ciprofloxacin,gentamycine,Norfloxacin and oxytetracycline that reach to (40,21,26,30 )mm zone of inhibition respectively . Thesame isolate revealed changes in results from resistant to sensitive to chloromphenicol ,Erythromycin andNaldixic acid that reach to (33,31,33)mm zone of inhibition respectively but its gave the same results for theantibiotics (Ampicillin,Bacitracin and cefixime).